Epidemiology and aetiology of traumatic cardiac arrest in England and Wales — A retrospective database analysis. (January 2017) - Barnard, Ed; Yates, David; Edwards, Antoinette; Fragoso-Iñiguez, Marisol; Jenks, Tom; Smith, Jason E.
Abstract: Background: Historically, reported survival from traumatic cardiac arrest (TCA) was extremely low. More recent publications have recorded survival to discharge of up to 8%. This improvement is likely to be multi-factorial; however, there are currently no published data describing the epidemiology or aetiology of TCA in England and Wales to guide future practice improvement. Methods: Population-based analysis of 2009–2015 Trauma Audit and Research Network (TARN) data. The primary aim was to describe the 30-day survival following TCA. Patients of all ages with traumatic cardiac arrest pre-hospital or in the emergency department (ED) were included. Data are described as number (%), and median [interquartile range]. Two-group analysis with Chi-squared test was performed. Results: During the study period 227, 944 patients were included in the TARN database. Seven hundred and five (0.3%) suffered TCA: 74.3% were male, aged 44.3 [25.2–83.2] years, ISS 29 [21–75], and 601 (85.2%) had blunt injuries. 612 (86.8%) had a severe traumatic brain injury and or severe haemorrhage. Overall 30-day survival was 7.5% (95%CI 5.6–9.5) — 'pre-hospital only' TCA 11.5%, 'ED only' TCA 3.9%, p < 0.02. No patients who were in TCA both pre-hospital and in the ED survived. Conclusion: This study has shown that short-term survival from TCA in this large civilian registry is 7.5%. Early and aggressive management of patients with TCA, using protocols that target the reversible causes of TCA, should be initiated. Further work to establish novel ways to manage patients with reversible causes of TCA is indicated. Resuscitation in this patient group is not futile.